Effect of rotation zero-crossing on single-fluid plasma response to three-dimensional magnetic perturbations. (14th February 2017) - Lyons, B C; Ferraro, N M; Paz-Soldan, C; Nazikian, R; Wingen, A
Abstract: In order to understand the effect of rotation on the response of a plasma to three-dimensional magnetic perturbations, we perform a systematic scan of the zero-crossing of the rotation profile in a DIII-D ITER-similar shape equilibrium using linear, time-independent modeling with the M3D-C1 extended magnetohydrodynamics code. We confirm that the local resonant magnetic field generally increases as the rotation decreases at a rational surface. Multiple peaks in the resonant field are observed near rational surfaces, however, and the maximum resonant field does not always correspond to zero rotation at the surface. Furthermore, we show that non-resonant current can be driven at zero-crossings not aligned with rational surfaces if there is sufficient shear in the rotation profile there, leading to amplification of near-resonant Fourier harmonics of the perturbed magnetic field and a decrease in the far-off-resonant harmonics. The quasilinear electromagnetic torque induced by this non-resonant plasma response provides drive to flatten the rotation, possibly allowing for increased transport in the pedestal by the destabilization of turbulent modes. In addition, this torque acts to drive the rotation zero-crossing to dynamically stable points near rational surfaces, which would allow for increased resonant penetration. By one or both of these mechanisms, this torque may play an important role in bifurcations into suppression of edge-localized modes. Finally, we discuss how these changes to the plasma response could be detected by tokamak diagnostics. In particular, we show that the changes to the resonant field discussed here have a significant impact on the external perturbed magnetic field, which should be observable by magnetic sensors on the high-field side of tokamaks but not on the low-field side. In addition, TRIP3D-MAFOT simulations show that none of the changes to the plasma response described here substantially affects the divertor footprint structure.